Permethrin-treated bed nets (mosquito nets) prevent malaria in Gambian children. - Snow, R; Lindsay, S; Hayes, R; Greenwood, B (1988)
The incidence of clinical attacks of malaria was significantly less in Gambian children aged 1-9 years who slept in villages where all the bed nets (mosquito nets) were treated with permethrin than in children who slept in control villages with placebo-treated nets. Significant differences in changes in spleen size and in packed cell volume were also observed between the 2 groups during the course of a rainy season. No side effect was noted. Treatment of bed nets with insecticide is a form of malaria control that is well suited to community participation and can readily be incorporated into primary health care programmes. Insecticide-treated nets may be more effective in areas of seasonal or low intensity transmission than in areas with heavy perennial challenge.